RELIGIOUS TEXT OF ‘PANATURAN’ - Maria Arina Luardini; Putu Sutama,; Natalina Asi (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2019)
The ethnic of Dayak Ngaju is one of the Dayaks in Central Kalimantan. This ethnic group has a native belief named Kaharingan, which is later on called as a religion. Kaharingan religion was previously called Ngaju beliefs, Hiden religion and even Kafir or unbelievers. In its process, in 1972, this belief is associated with Hinduism or Hindu Kaharingan. This religion has a holy book, Panaturan, in which most of the texts are used by most of the Dayak Ngaju community for religion purposes. To have a comprehensive picture of this religious text, this article used semantic structures to see the field and participants in the text. The findings show that Panaturan is structured within narrative, drama, and poetry. While, the participants on Panaturan are structured hierarchicaly from high – middle – low and textually called as upper realm/ sky, lower realm/ space, and earth.